2003
DOI: 10.1002/rra.721
|View full text |Cite
|
Sign up to set email alerts
|

Effects of discharge reductions on salt wedge dynamics of the Ebro River

Abstract: The Ebro River is the largest freshwater course of Spain with a discharge (in the lower course) that has been reduced in the last few decades due to the construction of several dams and the corresponding increase of water demand and river regulation. The lowest stretch of this river (about 42 km) behaves most of the time as a highly stratified estuary with a salt wedge. The dynamics of this salt wedge are important from the ecologic and economic points of view and depend mainly on the river discharge, although… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(32 citation statements)
references
References 8 publications
(5 reference statements)
0
30
0
1
Order By: Relevance
“…In addition, wind stress at the water surface has been ignored. Sierra et al (2004) in fact showed that wind action is not a dominant factor for salt wedge dynamics, even though it can play non-negligible secondary role.…”
Section: Numerical Modelmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, wind stress at the water surface has been ignored. Sierra et al (2004) in fact showed that wind action is not a dominant factor for salt wedge dynamics, even though it can play non-negligible secondary role.…”
Section: Numerical Modelmentioning
confidence: 99%
“…Interaction of fresh and salt water in an estuary is generally a very complex process, as explained in many research works (Arita and Jirka, 1987;Hodgins et al, 1977;Ralston et al, 2010;Schijf and Schonfeld, 1953;Sierra et al, 2004). In the case of strongly stratified estuaries, the salt circulation can be described with a relatively simple model, since salt transport results from a balance between horizontal and vertical advection of salt.…”
Section: Box Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, two-layer numerical models can adequately describe all relevant processes in salt-wedge estuaries if the stratification is strong enough to suppress the interfacial mixing, and the thickness of the interfacial layer is much smaller than the thickness of the upper and lower layer. In the past few years, several time-dependant two-layer numerical models (Liu et al, 2015;Ljubenkov, 2015;Sierra et al, 2004) were developed to describe the two-layer flow in salt-wedge estuaries. Although the main features of the stratified flow were captured by these models, they are not shock-capturing, and thus cannot correctly describe the internally transcritical flow which may occur under highly dynamical conditions due to sills or lateral contractions (Armi, 1986, Farmer andArmi, 1986).…”
Section: Introductionmentioning
confidence: 99%